2009
DOI: 10.1002/bjs.6613
|View full text |Cite
|
Sign up to set email alerts
|

Randomized clinical trial of anal fistula plugversusendorectal advancement flap for the treatment of high cryptoglandular fistulain ano

Abstract: Background:The aim of this randomized study was to compare the results of anal fistula plug and endorectal advancement flap in the treatment of high fistula in ano of cryptoglandular origin.Methods: Consecutive patients with high trans-sphincteric fistula in ano of cryptoglandular aetiology were randomized to treatment with either an anal fistula plug or endorectal advancement flap. Patients agreed to participate in a follow-up programme, which included scheduled visits at 2, 4, 8, 12 and 24 weeks and at 1 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
85
2
17

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(109 citation statements)
references
References 20 publications
5
85
2
17
Order By: Relevance
“…The early experience with the anal fistula plug was very promising, but more recent studies have shown success rates from 20% to 34%, which are consistent with our results. 9,14,15,25,26,30 Two retrospective studies and 1 randomized prospective study compared anal fistula plugging with endorectal fistula in patients with transsphincteric fistulas. 25,26,30 In all 3 studies, the endorectal advancement flap had a better outcome with a success rate of 62% to 88% compared with the 20% to 34% seen with the plug.…”
Section: Commentmentioning
confidence: 99%
“…The early experience with the anal fistula plug was very promising, but more recent studies have shown success rates from 20% to 34%, which are consistent with our results. 9,14,15,25,26,30 Two retrospective studies and 1 randomized prospective study compared anal fistula plugging with endorectal fistula in patients with transsphincteric fistulas. 25,26,30 In all 3 studies, the endorectal advancement flap had a better outcome with a success rate of 62% to 88% compared with the 20% to 34% seen with the plug.…”
Section: Commentmentioning
confidence: 99%
“…However, the literature mentions a high rate of recurrences and infective complications (sepsis, suppuration, or abscesses) following the use of such devices in anorectal conditions [3,4]. It is not unreasonable to expect some of these complications or recurrences when the plug is being used in a recto-urethral repair as well.…”
Section: Editormentioning
confidence: 99%
“…The mean time to recurrence has been found to range widely from a median of 8 weeks to 9 months [ 10 -12 ]. Some studies show the majority of recurrences occurring within the fi rst year [ 13 ], or even all recurrences occurring within the fi rst 3 months [ 14 ], while other studies have shown recurrences up to 55 months after surgery [ 7 , 15 ]. Studies designed specifi cally to examine the length of follow-up needed to capture all recurrences demonstrate that the majority of recurrences occur early.…”
Section: Healing Of Fistulamentioning
confidence: 99%